Anencefalia, macroglossia e fenda labial em cão: relato de caso - Wammes, Jéssica Caroline Staffen; Filadelpho, André Luis; Birck, Arlei José; Peres, Jaime Augusto; Silva, José Ricardo de Carvalho Pinto e [UNESP]; Guazzelli Filho, Joffre [UNESP]; Barcelos, Rodrigo Patera (My University, 2013)
Anencephaly refers to a malformation caused by abnormal neurulation, resulting in the absence of fusion of the neural folds and training of the neural tube in the region of the brain. Macroglossia is a disturbance of multiple etiology, classified as true or relative, and can be congenital or acquired. The cleft lip is due to the lack of fusion of tissues of the upper lip.

Anencefalia refere-se a uma malformação congênita originada de uma neurulação anormal, resultando na ausência de fusão das pregas neurais durante a formação do tubo neural na região do encéfalo. A macroglossia é um distúrbio da formação de etiologia múltipla, classificada como verdadeira ou relativa, podendo ser congênita ou adquirida. A fenda labial é decorrente da falta de fusão dos tecidos do lábio superior.
Congenital malformations in dog: case report
Keywords: Anencephaly; Macroglossia; Cleft lip; Malformation; Dog; Anencefalia; Macroglossia; Fenda labial; Malformação; Cão